Черная рука из второго подъезда: сказки / И. Востросаблин - Востросаблин Иван (Сказки нашего двора, 2001)
Экземпляры: ф.12 (20150806) / Инвентарный номер: 048107 / Цена: 55.00 / Авт.знак: В 78 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6